Topic specific epistemic beliefs: Extending the Theory of Integrated Domains in Personal Epistemology. (August 2018) - Merk, Samuel; Rosman, Tom; Muis, Krista R.; Kelava, Augustin; Bohl, Thorsten
Abstract: Two studies were conducted to extend the Theory of Integrated Domains in Epistemology framework (TIDE; Muis, Bendixen, & Haerle, 2006) with regard to the level of topic-specificity and to empirically test crucial aspects of this extension. In Study 1, 212 student teachers were surveyed on their general and topic-specific absolute beliefs regarding eleven topics. Topic familiarity and students' teaching subjects were investigated as person-specific context factors. In Study 2, domain-specific and topic-specific multiplistic beliefs of 365 student teachers were investigated. The topic-specific context was experimentally manipulated; Students were presented with four texts on educational research whose content (invariant over the conditions) allegedly originated from a layperson, an expert, or a scientist. The results provide evidence for the assumption of a reciprocal influence between topic-specific and more general epistemic beliefs. Furthermore, we found substantial effects of topic-related contextual factors on topic-specific epistemic beliefs. Implications for theory and suggestions for future empirical research are discussed. Highlights: Theory of Integrated Domains in Epistemology (TIDE) framework was extended to the level of topic-specificity. Two studies provide evidence for a reciprocal influence between topic-specific and more general epistemic beliefs. Experimentally varied contextual factors influenced topic-specific epistemic beliefs substantially.